Quality analysis and culinary utilization of cashew apple (Anacardium occidentale L.) - Neethu Mohan (Department of Home Science, College of Agriculture, 2016)
The present investigation entitled “Quality analysis and culinary utilization of cashew apple (Anacardium occidentale L.)” was conducted at the Department of Home Science, College of Agriculture, Vellayani, during the period October 2015 – May 2016. The objective of the study was to analyze the qualities of cashew apple and to evaluate its use in culinary preparations. Cashew apple needed for the study was procured from State Seed Farm, Kottarakara, Instructional Farm, College of Agriculture, Vellayani and also from local sources. The collected Cashew apple was pre-treated to remove the astringent content by steaming for 5 minutes under pressure (T1), boiling in 2 per cent salt solution for 5 minutes (T2), immersing fruit in rice gruel extract for 30 minutes (T3), immersing fruit in 0.55 per cent gelatin solution for 10 minutes (T4) and immersing fruit in 5 per cent salt solution for 3 days with the change of salt solution daily (T5). Fresh cashew apple served as control (T6). After the pre - treatment process, samples were subjected to physical, chemical and nutrient analysis. Based on the analysis of samples the treatment with least content in astringent principles (polyphenol and tannin) and with highest sensory scores were selected and stored in glass containers under refrigeration for storage study. Physical appearance and colour, fruit flavour, texture, taste and overall acceptability of treated and fresh cashew apples were evaluated by a panel comprising of 10 members using a 5 point score card. Based on the mean scores, the best treatment was identified which was T2 (Cashew apple treated in 2 per cent salt solution for 5 minutes). Chemical analysis of fresh and treated Cashew apple observed that a reduction in the chemical constituents in treated Cashew apples compared to T6 (Fresh cashew apple). It was found thatT2was in least content in polyphenol (0.11 per cent) and tannin (0.07per cent) hence selected for further in depth study. Nutrient analysis showed that the values obtained for different nutrients were lower for treated cashew apple. T2 sample got comparatively higher values than other treatments in carbohydrate (11.30g) vitamin C (180.00mg) and potassium (75.20 mg) and was also on par with control (T6). Treated cashew apple sample T2 and control T6 were stored in glass containers under refrigeration for storage study. The study showed no significant change in moisture content of the stored samples. With respect to acidity,T6 showed significant increase but not in T2. Microbial growth was seen in T2 sample on the 5th day and in T6 sample on the 7th day of storage. Cashew apple powder was also prepared from selected treatment T2 and fresh cashew apple T6 and denoted as T2P and T6P which was also used in culinary preparations. Four types of culinary preparations such as Cashew apple gravy preparation (Masala curry), Cashew apple salad, Cashew apple sweet chutney and Cashew apple sweet meat product (payasam) were made from T2andT6. Sensory acceptability of these preparations was tested by 10 panel members using 5 point score card and preference was assessed using 9 point hedonic rating scale. These four preparations were also made using cashew apple powderT2P and T6P and evaluated. Results of the organoleptic evaluation of culinary preparations from T2, T6, T2P and T6Psecured highest mean preference score for cashew apple salad (8.8/9) prepared from T2 followed by Cashew apple payasam (8.7/9) from T6 and Cashew apple chutney (8.7/9) from T2P. Cashew apple masala curry got (8.6/9) from T2. From the above findings, it can be concluded that Cashew apple treated with 2 per cent salt solution (T2) lower the astringent principle and was found to be most suitable for culinary preparations such as sweet meat products, gravy preparations, chutneys and fresh salads.